Magnetite-epoxy nanocomposites obtained by the reactive suspension method: Microstructural, thermo-mechanical and magnetic properties. (September 2017) - Barrera, G.; Sciancalepore, C.; Messori, M.; Allia, P.; Tiberto, P.; Bondioli, F.
Graphical abstract: Highlights: A single organic agent is exploited in the whole preparation process. Magnetic nanoparticles form aggregates in polymeric nanocomposites. Size and nature of magnetic aggregates depend on synthesis parameters. Abstract: Magnetite nanoparticles are prepared by non-hydrolytic sol-gel process in the presence of iron(III)-acetylacetonate as precursor and 2-ethyl-1, 3-hexanediol as reactive solvent; the nanoparticle size is affected by the precursor-to-solvent ratio. The suspensions, mixed with bisphenol-A diglycidyl ether, are cured in the presence of ytterbium(III) trifluoromethanesulfonate as cationic initiator. The chain-growth polymerization results in a three-dimensional network where the diol, acting at the same time as reactive solvent and suspending medium, is covalently linked to the epoxy network according to the "activated monomer" mechanism. The filler induces stiffening because of hydrodynamic effects and of a better cross-linking ability in the nanocomposite. Magnetite nanoparticles form aggregates whose size and shape depend on concentration. Isothermal magnetization loops and FC/ZFC DC susceptibility curves indicate that all nanocomposites are dominated by interparticle magnetic interactions resulting in a collective response whose details depend on nanoparticle concentration and degree of aggregation.